Effect of elevated temperature on the compressive strength and durability properties of crumb rubber engineered cementitious composite - Mohammed, B.S. (MDPI AG, 2020)
This paper reports the findings of the effect of elevated temperature on the compressive strength and durability properties of crumb rubber engineered cementitious composite (CR-ECC). The CR-ECC has been tested for its compressive strength and chemical resistance test against acid and sulphate attack. Different proportions of crumb rubber (CR) in partial replacement to the fine aggregate and polyvinyl alcohol (PVA) fiber have been utilized from 0 to 5 and 0 to 2. The experiments were designed based on a central composite design (CCD) technique of response surface methodology (RSM). After 28 days curing, the samples were preconditioned and exposed to high temperatures of 100 °C, 200 °C, 300 °C, 400 °C, 500 °C, 600 °C, 700 °C, 800 °C, 900 °C, and 1000 °C for one hour. Although the residual compressive strength of CR-ECC was negatively affected by elevated temperature, no explosive spalling was noticed for all mixes, even at 1000 °C. Results indicated that CR-ECC experiences slight weight gain and a reduction in strength when exposed to the acidic environment. Due to the reduced permeability, CR-ECC experienced less effect when in sulphate environment. The response models were generated and validated by analysis of variance (ANOVA). The difference between adjusted R-squared and predicted R-squared values for each model was less than 0.2, and they possess at least a 95 level of confidence. © 2020 by the authors.